2014
DOI: 10.1074/jbc.m114.581397
|View full text |Cite
|
Sign up to set email alerts
|

G Protein and β-Arrestin Signaling Bias at the Ghrelin Receptor

Abstract: Background:The G protein coupled receptor GHSR1a mediates feeding and addictive behaviors. Results: Mutagenesis of the second intracellular loop of GHSR1a generates biased receptors, favoring distinct signaling events. Conclusion: Receptor conformations that support signaling bias at the wild-type receptor should exist. Significance: Recapitulating signaling bias at GHSR1a may facilitate the identification of novel selective therapies to treat addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 71 publications
6
74
0
Order By: Relevance
“…Previous work in cellular systems supported a critical role for the GHSR C-terminal domain in receptor trafficking (18,19). Here, several lines of evidence support the notion that the distal part of the C-terminal tail of GHSR inhibits GHSR function.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Previous work in cellular systems supported a critical role for the GHSR C-terminal domain in receptor trafficking (18,19). Here, several lines of evidence support the notion that the distal part of the C-terminal tail of GHSR inhibits GHSR function.…”
Section: Discussionsupporting
confidence: 78%
“…This hypothesis is supported by another mutant GHSR (GHSR-P148A), which cannot interact with β-arrestin 2 but is still internalized in response to agonist stimulation, and shows increased agonist-induced G protein-dependent signaling (19). In the absence of ligand, however, the wild-type GHSR and GHSR-Q343X isoforms showed similar basal MAPK-and RhoA-dependent signaling, indicating that the Q343X mutation does not modify constitutive signaling.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…1 and 2, A and B). Because it was reported that GHS-R1a activated ERK1/2 through G q/11 , G i , and arrestin-dependent pathways (28,43,44), we tested the efficacy of our ligands toward ERK1/2 activation. All compounds displayed comparable efficacy to promote ␤-arrestin2 recruitment (Table 2 and Fig.…”
Section: Efficacy Of Ghs-r1a Ligands Toward ␤-Arrestin2mentioning
confidence: 99%